The Returns to Parental Health: Evidence from Indonesia - Dara Lee Luca; David E. Bloom (Institute of Labor Economics (IZA), 2018)
This paper investigates the economic returns to parental health. To account for potential endogeneity between parental health and child outcomes, we leverage longitudinal microdata from Indonesia to estimate individual fixed effects models. Our results show that the economic returns to parental health are high. We show that maternal health not only significantly affects her children's health, but is also intrinsically linked to her spouse's labor market status and earnings. Paternal health appears to be more linked to child schooling outcomes, especially for girls. When both parents are in poor health, the negative effects on their children are compounded. Additionally, the consequences of poor parental health are enduring. Longer-run effects of poor parental health manifest in a lower likelihood of high school completion, fewer years of schooling, and poorer adult health.
Keywords: I12; J13; J16; 330; parental health; spousal health; child health; education; family economics